A (re) produção do espaço urbano nas pequenas cidades da Amazônia setentrional: um estudo sobre Bonfim - RR - Barbosa, Tânia Maria Sena (2015)
This dissertation is based on a study of the small towns of the Northern Amazon, specially Bonfim-RR in the context of reproduction of urban space. Thus, the objective of this research was to conduct a study on the reproduction of urban space in the small towns of the Northern Amazon, highlighting the city of Bonfim as a case study in the context of Roraima. The specific objectives include understanding through the use of questionnaires and interviews, urban growth of Bonfim – from 1970 to 2014. It is understood that the man as an agent (re) that organizes the space, has been generating socio-spatial transformations often according to their needs. In this perspective, we seek to contribute to the understanding of the small towns in the Amazon, since there are few studies about them. It is hoped that this research will also help to understand the nature and trends of urban hierarchy of the region and the new forms and functions of urban small towns in northern Amazonia, thus increasing the scientific research in the different lines, particularly in the constitution of Geographic Science.